Assessing the effect of foodborne endocrine disruptors exposure on methionine synthase activity in neuro-2a neuroblastoma cell lines - Gabriela García-Cerón; Alba Fernanda Solano-González; Iván Hazael Bello-Cortés; Ileana Andrea Bonilla-Brunner; Daniela Araiza-Olivera; Manuel Gutiérrez-Aguilar; Yazmin Ramiro-Cortés; Marcos Francisco Rosetti; Roeb García-Arrazola (All Life)
In the present study, in vitro neuronal cell cultures were exposed to the two most common varieties of EDCs reported in food, phthalates and bisphenol A (BPA). Specifically, Bis (2-ethylhexyl) phthalate (DEHP), Mono-butyl-phthalate (MBP), Di-n-octylphthalate (OP), and Bisphenol A (BPA) were exposed in Neuro-2a neuroblastoma cell line. The enzymatic activity of methionine synthase (MS) was reduced by up to 3-fold in comparison to cultures that were not exposed to EDCs. MS is the key enzyme in the metabolic pathway that has been proposed elsewhere to be related to redox/methylation related disorders.